Customer Trust and Interaction Quality as a Mediating: The Effect of Quality of Information on Purchase Decision - Pratondo, Kalistya Rizki; Marsudi, Marsudi; Wijaya, Rahmad (University of Muhammadiyah Malang, 2023)
E-retail has one of the problems, such as not being able to provide examples of goods products that consumers want in digital form; therefore, this affects consumer purchasing decisions. Many factors underlie consumer purchasing decisions in e-retail. This study aims to analyze the role of customer trust and interaction quality in mediating the influence of quality of information on purchase decisions in electronic retail (E-Retail). The population in this study is e-retail users aged 18 years and over who have used or are currently using e-retail. The sample used was 100 people. The analysis technique uses Partial Least Square (PLS). The results showed that quality of information influences purchasing decisions and customer trust, customer trust influences purchasing decisions, quality of information influences interaction quality, and interaction quality influences purchasing decisions and customer trust. It was also found that customer trust and interaction quality can mediate the influence of quality of information on purchasing decisions.